2017
DOI: 10.1038/ijo.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in infancy are associated with child diet and weight outcomes at 6 years

Abstract: Early decisions about milk-feeding, and the types of solid foods offered in infancy can foreshadow dietary patterns and obesity risk later in childhood. Infants who were offered energy-dense foods had higher intake of these foods at 6 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 25 publications
1
53
0
4
Order By: Relevance
“…Consistent with our pre-specified hypothesis, we found that more frequent intake of unhealthy foods during complementary feeding was associated with higher WFL z-scores, which is similar to other studies conducted with infants and children. 31,32 . Although few mothers introduced unhealthy foods like french fries, snacks, and sweets before 4 months of age, frequent intake of unhealthy foods (>1 serving/d) during the complementary feeding period was common (71% of the sample) and associated with higher WFL z-scores.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our pre-specified hypothesis, we found that more frequent intake of unhealthy foods during complementary feeding was associated with higher WFL z-scores, which is similar to other studies conducted with infants and children. 31,32 . Although few mothers introduced unhealthy foods like french fries, snacks, and sweets before 4 months of age, frequent intake of unhealthy foods (>1 serving/d) during the complementary feeding period was common (71% of the sample) and associated with higher WFL z-scores.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from longitudinal studies has revealed the importance of early dietary patterns on later dietary behaviors and health outcomes. [23][24][25][26][27][28] For example, young children who had infrequent consumption of fruits and vegetables at 11 months of age continued to have infrequent consumption 6 years later. 24 A 2015 American Academy of Pediatrics Clinical Report calls on pediatricians to play an active role in obesity prevention with a focus on starting before 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the role of dietary patterns in early childhood as a determinant of obesity risk [18]. Diets of poor quality might be important, as they are often characterized by high consumption of energydense foods [19][20][21]. Children with higher intakes of food from unhealthy patterns showed an increase in total and central body adiposity [22].…”
Section: Introductionmentioning
confidence: 99%